Conceptualization of natural heritage in the context of the ecosystem approach (Research Announcements "Heritage BG", 2025)
The article aims to explore natural heritage as a socio-ecological phenomenon. The definitions and cycle of development of the concept of natural heritage is explained. The process of provision and demand of ecosystem services that benefit socio-environmental systems is presented to illustrate how an element of the natural system becomes natural heritage. As a result of the analysis, the authors propose a definition of ‘natural heritage’ in the context of an ecosystem-based approach. The results would support the sustainable use of natural heritage sites for the development of nature-based tourism. References:Georgiev 2005: Georgiev, Georgi. Kriterii i indikatori za rekreatsionna otsenka na biologichnoto raznoobrazie na zashtitenite teritorii v Balgariya, Problemi na geografiyata, kn. 3-4, BAN, Sofiya, Balgariya, 65-68.Gurkov et al. 2013: Gurkov, Rosen, Galev, Emil, Perchiklijski, Grigor and Ivan Golomehov. Evropeyska Konventsiya za Landshafta. Vavezhdane v Balgariya AGENTSIYA DEYTA-SPP SPP, Sofia, 1-25.EKL 2005: Evropeyskata konventsiya za landshafta. DV br. 22 ot 15 mart 2005.Nikolova et al. 2020: Nikolova, Mariyana, Nedkov, Stoyan and Biliyana Borisova. Prirodno nasledstvo i rekreacionni ekosistemni uslugi, SocioBrains, Issue 66, 1-8. http://sociobrains.com/Popova 1993: Popova, Nikolina. Prirodni rekreatsionni resursi, Univ. izd. ‘Sv. Kliment Ohridski’, Sofia, 1 127.Tomova, Borisova 2018: Tomova, Каtrin and Biliyana Borisova. Biosfernite parkove po programata ‘Chovekat i biosferata’ na YUNESKO kato instrument za regionalno razvitie i osaznavane na palniya nabor ot ekosistemni uslugi (na primera na Tsentralen Balkan). Godishnik na SU ‘Sv. Kliment Ohridski’, kn. 2, tom 110. 123-144.Toncheva 2014: Toncheva, Тоdorka. Vliyanie na bioraznoobrazieto varhu razvitieto na turizma, Avangard Prima, Sofia, 1-98.Vasileva 2018: Vasileva, Vanya. Prirodni turisticheski resursi na Balgariya, Shumen.De Groot et al. 2002: de Groot, Rudolf, Matthew Wilson and Boumans Roelof. A Typology for the Classification, Description and Valuation of Ecosystem Functions, Goods and Services. Ecological Economics 41 (3), 393-408.Haines-Young, Potschin 2013: Haines-Young, Roy and Marion Potschin. Common International Classification of Ecosystem Services (CICES) V 4.3: Consultation on Version 4, August-December 2012. EEA Framework Contract No EEA/IEA/09/003, Available from https://biodiversity.europa.eu/maes/common-international-classification-of-ecosystem-services-cices-classification-version-4.3.Haines-Young, Potschin 2017: Haines-Young, Roy and Marion Potschin. Common International Classification of Ecosystem Services (CICES) V5.1 and Guidance on the Application of the Revised Structure. Available from www.cices.eu.Havinga, Bogaart, Hein, Tuia 2020: Havinga Ilan, Patrick Bogaart, Lars Hein and Devis Tuia. Defining and Spatially Modelling Cultural Ecosystem Services Using Crowdsourced Data, Ecosystem Services, Volume 43, June 2020, 101-091.Georgiev 2006: Georgiev, Georgi. Nyakoi problemi na rekreatsionnoto usvoyavane na zashtitenite teritorii v Balgariya http://oldweb.ltu.bg/jmsd/files/articles/14/14-29 _G_Georgiev.pdfGordon 2018: Gordon, John. Geoheritage, Geotourism and the Cultural Landscape: Enhancing the Visitor Experience and Promoting Geoconservation, Geosciences, 8 (4), 136 https://doi.org/10.3390/geosciences 8040136Ihtimanski et al. 2020: Ihtimanski Ivo, Stoyan Nedkov and Lidiya Semerdzhieva. Mapping the Natural Heritage as a Source of Recreation Services at National Scale in Bulgaria, One Ecosystem 5, https://doi.org/10.3897/oneeco.5.e54621Nedkov et al. 2021: Nedkov, Stoyan, Mariana Nikolova, Radenka Mitova, Bilyana Borisova, Dessisslava Hristova, Lidiya Semerdzhieva, Miglena Zhiyanski and Hristina Prodanova. Prioritization of Ecosystem Services Related to the Natural Heritage in Bulgaria, JBGS, Pentsoft, (in print).Nikolova et al. 2021: Nikolova Mariana, Stoyan Nedkov, Bilyana Borisova, Velimira Stoyanova and Radenka Mitova. Cultural Ecosystem Services Provided by Natural Heritage Sites in Karst Territories of Smolyan Region, Bulgaria (in this volume).Osipova et. al. 2014: Osipova, E., Wilson, L., Ralph Blaney, Yachuan Shi, Max Fancourt, Strubel, M., Salvaterra, T., Brown, C. and B. Verschuuren, The Benefits of Natural World Heritage: Identifying and Assessing Ecosystem Services and Benefits Provided by the World’s Most Iconic Natural Places. Gland, Switzerland: IUCN. vi + 58.Selicato 2016: Selicato, Francesco. The Concept of Heritage. In: Rotondo F., Selicato F., Marin V., Lopez Galdeano J. (eds.) Cultural Territorial Systems. Springer Geography. Springer, Cham. https://doi.org/10.1007/978-3-319-20753-7_2Sinnyovsky 2011: Sinnyovsky, Dimitar. Geoconservation and the Geological Heritage of Bulgaria. Journal of the Bulgarian Geological Society, year 72, vol. 1–3, 99-110.Thurney 2005: Thurney, Simon. Into the Future. Our Strategy for 2005-2010. In: Conservation Bulletin English Heritage (49), 25 – 26. Retrieved from https://historicengland.org.uk/images-books/publications/conservation-bulletin-49/cb-49/Tengberg et al. 2012: Tengberg, Anna, Fredholm, Susanne, Eliasson, Ingegard, Knez, Igor, Saltzman, Katarina and Ola Wetterberg. Cultural Ecosystem Services Provided by Landscapes: Assessment of Heritage Values and Identity, Ecosystem Services, 2012, http://dx.doi.org/10.1016/j.ecoser.2012.07.006.Sites:CEU 2019: Central European University. The Concept and History of Cultural Heritage. Avilable at: https://medievalstudies.ceu.edu/concept-and-history-cultural-heritageCultural Heritage Act, 2009 adopted Official Journal No.19/13.03.2009, amend. OJ. 17/26. 02. 2021 https://en.unesco.org/sites/default/files/bulgaria_culturalheritageact_2009_entof.pdfWorld Heritage Convention, 1972. UNESCO World Heritage website: http://whc.unesco.org/
Keywords: natural heritage; ecosystem services; socio-environ mental systems